Hubungan Antara Lemak Subkutan, Indeks Massa Tubuh, Kadar Hemoglobin Dengan Dismenore Primer Pada Remaja Putri Di SMAN 1 Sumberpucung - Aisa Oktaviana Nur Imaniar; Erni Dwi Widyana; Ita Yuliani (Jurnal Pendidikan Kesehatan, 2019)
Dysmenorrhea is pain experienced by teenagers during menstruation. Based on the level of pain, dysmenorrhea is divided into 2, primary dysmenorrhea and secondary dysmenorrhea. Primary dysmenorrhea occurs in adolescence, about 2 until 3 years after the first menstruation, pain originating from uterine contractions stimulated by prostaglandins. Risk factors for dysmenorrhea can be caused by menarche at an early age, nutritional status, family history, coffee consumption, fast food habits. Adolescents with a body mass index more than normal have high levels of prostaglandins that can lead to primary dysmenorrhea. Adolescents with anemia or less than normal hemoglobin level, feel dysmenorrhoeic pain or pain during menstruation. The purpose of this study was to determine the relationship of subcutaneous fat, body mass index, hemoglobin level with primary dysmenorrhea in adolescent girls. The population in this study was 44 people, sampling is done by total sampling. Hypothesis testing using Chi Square test T approximately same as 0,05 and logistic regression. The results of logistic regression test found that there was a correlation between subcutaneous fat namely 0.004 is smaller than 0.05 and hemoglobin level namely 0.008 is smaller than 0.05 while for body mass index, there was no correlation with primary dysmenorrhea namely 0.152 is greater than 0.05. It is hoped that this research can be further developed regarding other risk factors for primary dysmenorrhea in young women.